(untitled) (Applied Biological Research, 2025)
In Mizo traditional medicine, the scholar tree (Echites scholaris) is used as a therapy for various illnesses, including blood disorders and malarial infection. To evaluate its antimalarial properties, bark extracts were prepared using solvents of differing polarities (chloroform and petroleum ether). The plant extracts were tested against two strains of the human malarial parasite: a drug-sensitive Plasmodium falciparum (Pf3D7) and a multidrug-resistant strain (PfK1). The extracts showed effectiveness against both strains.The chloroform-based extract exhibited high activity, with half-maximal inhibitory concentration (IC₅₀) values of 14.0 µg mL⁻¹ against Pf3D7 and 10.0 µg mL⁻¹ against PfK1. The petroleum ether-based extract was slightly less potent, showing IC₅₀ values of 22.0 µg mL⁻¹ (Pf3D7) and 26.7 µg mL⁻¹ (PfK1). In terms of drug resistance potential, the petroleum-based extract exhibited an extremely low level of resistance (Ri = 1.2), while the chloroform-based extract showed no resistance (Ri < 1).Cytotoxicity testing against VERO C1008 cells revealed that the plant extracts were highly safe, with half-maximal cytotoxic concentrations (CC₅₀) far exceeding the toxicity threshold. Gas chromatography–mass spectrometric analysis identified cis-3-hexenyl acetate and 3-decyn-2-ol as major phytocompounds in the chloroform-based extract, while linoelaidic acid, phthalic acid, and 2-ethylbutyl nonyl ester were predominant in the petroleum ether-based extract. Computational binding studies against vital proteins such as Plasmodium falciparum erythrocyte membrane protein 1 (VAR2CSA) and S-adenosyl-L-homocysteine hydrolase (SAHH) indicated high ligand-binding capacity. This study validates the antimalarial application of the plant and provides a rationale for further molecular and pharmacological investigations.